Rancang Bangun Aplikasi Sistem Informasi Lembaga Keuangan Mikro Syariah Berbasis Web - Hasna Zakiyah Fadilah; Hasbi Assidiki Mauluddi; Djoni Djatnika (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
In the industrial revolution 4.0, efforts to use digital-based financial technology are very much needed with a form of encouragement to continue to innovate in digital financial services. However, with the large potential for the development of Sharia Cooperatives in Indonesia, there are still many who do not have a digital-based financial information system. It is not uncommon for sharia cooperative institutions to have problems in recording financial information systems such as data loss, inaccurate data and so on. For that we need a system that can record accurately and efficiently in order to assist Sharia Cooperatives in recording information systems and financial reports. This study aims to create a financial information system application and try it in the West Bandung Mutual Cooperation Sharia Cooperative in the hope that it will simplify the work and clarify the information system in the Sharia Micro Finance Institution, especially the Mutual Cooperation Sharia Cooperative. This study uses Research and Development (R&D) research methods with several stages consisting of field studies, problem formulation, research objectives setting, data collection & processing and data analysis. These four stages function to find out the shortcomings and things that the company needs. After that the research continued with system design in accordance with the information that had been obtained from the previous stage. Then after the system has been created, a trial is carried out with the black box testing technique with the results of the system running 100% as expected. After the trial, it enters the evaluation stage by distributing questionnaires with questions originating from the Technology Acceptance Model (TAM) analysis which will produce a descriptive analysis with the conclusion that the application designed is included in the very good category so that it is feasible to use.